MO471: Adverse Drug Reactions and Drug–Drug Interaction in Chronic Kidney Disease With Tuberculosis. (3rd May 2022) - Datta, Divya; Attur Prabhu, Ravindra; Abdul Khader, Nisha; Prasad Nagaraju, Shankar; Ramachandra Rao, Indu; Vinayak Shenoy, Srinivas; Rangaswamy, Dharshan; Bhojaraja, Mohan V; Thunga, Girish; Magazine, Rahul; Shetty, Raghavendra
Abstract: BACKGROUND AND AIMS: The risk of developing tuberculosis (TB) is 10–25% in chronic kidney disease (CKD) patients. TB in CKD patients may have a mortality of 16–37%. Standard treatment with four drugs (Isoniazid, Rifampin, Pyrazinamide and Ethambutol) predisposes to side effects, drug interactions and incomplete adherence in this population. We studied adverse drug reactions and potential drug–drug interactions in CKD patients with TB. METHOD: Consecutive patients with CKD and TB attending tertiary care hospitals in South India were included over a period of 12 months. CKD was diagnosed based on estimated GFR using CKD EPI and TB using standard methodology. Data on demographic details and adverse drug reactions were collected from case records. Potential drug–drug interactions were checked using Micromedex Drug-Reax ® (Truven Health Analytics, Greenwood Village, Colorado, USA). Statistical analysis was done using SPSS version 20. RESULTS: Of 1300 TB patients, 59 had CKD. The demographic details are as per Table 1 . CONCLUSION: In CKD with TB, adverse drug reactions were seen in 45.5% and potential drug–drug interactions were seen mostly with rifampin (28.81% in CKD).